Graphene quantum dots for biological applications - Ananthanarayanan, Arundithi (2016)
Graphene quantum dots (GQDs) have emerged as a new class of superior fluorescent materials owing to their unique properties of small size, biocompatibility, photostability, water solubility and large surface area. In this thesis various synthesis methods for GQDs for diverse applications have been developed and the fluorescence mechanisms of GQDs have been explored. A novel and high throughput synthesis approach for blue-luminescent GQDs from 3D freestanding graphene has been demonstrated. The as-synthesized GQDs are used as fluorescence turn-off sensor for ferric ions with a lower theoretical detection limit of 7.22 μM. Heteroatom doping in graphene and GQDs has known to introduce new and enhanced properties. In this regard, a two-step synthesis protocol for nitrogen and phosphorous co-doped GQDs for in-vitro bioimaging is developed. The GQDs show a high quantum yield of 28% and a high two-photon absorption cross-section of 20000 GM. Taking advantage of GQDs as excellent carriers for hydrophobic and amphiphilic drugs, GQDs synthesized by a new mechanical synthesis strategy via ball-milling are employed as carriers for the hydrophobic drug β-lapachone. The GQD-drug conjugates exhibit a pH dependent release behavior. They also exhibit enhanced cytotoxicity as compared to free drug in two different cancer cell lines in-vitro. The poorly understood photoluminescence mechanisms of GQDs have been investigated by theoretical calculations using density-functional theory (DFT) and time-dependent DFT. The results indicate that fluorescence of a GQD is greatly influenced by its size, edge configuration, shape and attached chemical functionalities. In addition, it is also observed that fluorescence properties of large GQDs consisting of heterogeneously hybridized carbon network is dependent largely on small sp2 clusters isolated by sp3 carbons.